A Conceptual Framework for Analysing Admission Policy: A Case Study of Recent Developments in Germany’s Asylum Policy - Schneider, Claudia (Two Homelands, 2017)
Germany’s asylum policy and the debate surrounding it underwent a significant shift in 2015 when asylum applications increased considerably over previous years. Rather than moving towards more restriction, as was the case in the past when asylum applications saw a substantial rise, the German government responded towards refugees in an open and welcoming manner. This article will analyse the developments which led to the German government’s “we can manage it” response, using a conceptual framework which considers structural and agency concerns and the interconnection between the two. The framework centres on processes within the party political system and the way they were or were not influenced by developments and structures in the wider socio-political and economic environment and by politicians’ perceptions, beliefs and goals. The findings show that a new alliance was formed between the conservative CDU party and the social democratic SPD party, reflecting a political debate on asylum seekers and refugees which combined an explicit humanitarianism within Germany with a hierarchical classification of migrants who were “more or less needy” of protection, limiting the explicit humanitarianism within Germany to specific groups of migrants and refugees.